ASSESSMENT OF LEAD AND CADMIUM IN POWDERED EYE SHADOW SOLD IN LOCALLY MARKETED IN BAQUBA, DIYALA, IRAQ (World Bulletin of Public Health, 2022)
It has been proven that many consumer products such as cosmetics are contaminated with varying levels of heavy metals. So, in this study we evaluated the level of heavy metals like lead(Pb) and cadmium(Cd) in cosmetic products sold in locally marketed in Baquba, Diyala, Iraq. The cosmetic items included Eye Shadow. The eye makeup was analyzed in triplicate using aflame atomic absorption spectrophotometer (FAAS). After they have been analyzed. The results revealed that the level of Lead in the samples ranged from (
Keywords: Environmental pollution; Eye shadow; Lead; Cadmium